Grassland management for stem-boring insects: Abandoning small patches is better than reducing overall intensity - Rothenwöhrer, Christoph; Scherber, Christoph; Tscharntke, Teja (Agriculture, ecosystems & environment, 2013)
► Stem-borer communities among habitats varying in disturbance frequency were compared. ► Reducing management over a 1-season period is not sufficient to enhance insect abundances. ► Species mostly responded positively to grassland abandonment of 2-seasons or more. ► Regular land-use management narrows species’ spatial niche width. ► Small grassy strips should be excluded from grazing or mowing for at least two growing seasons. Grasses are a dominant component of meadows and pastures, harboring an often overlooked diversity of non-pest stem-boring insects that feed and develop exclusively enclosed by plant tissue inside grass shoots. Surprisingly, the effects of land-use management on these highly specialized communities have rarely been studied. Here, the applicability of short-term management reduction as a conservational tool, increasing stem-borer colonization success, was examined. On 41 grasslands in Germany a temporal gradient of set-aside treatments was established by experimentally excluding subplots from management, or by a priori selection of already abandoned grassland patches. Stem-borer abundances and attack heights on resulting managed, 1-season unmanaged and ≥2-seasons abandoned treatments were compared. Grassland management had a negative effect on stem-borer colonization success and spatial niche differentiation. Reducing management over a 1-season period did not enhance abundances. Two out of three species responded positively only to an abandoning treatment lasting ≥2-seasons, which was also reflected by the decreasing spatial overlap in this treatment. Even though grass shoots in unmanaged areas were on average 14.9cm taller than in managed areas, stem-borer abundances did not differ between the latter treatments. Hence, preserving essential larval development and hibernation habitats in future rotational set-aside schemes requires a management exclusion period of at least two growing seasons. From these grassy strips, e.g. located at meadow edges, highly specialized stem-borers can re-colonize sward islets on surrounding intensively managed grasslands, despite of ever changing land-use practices and environmental conditions.